Daya Serap CO2 Tanaman Pengisi Ruang Terbuka Hijau Pada Zona Riparian di Kali Surabaya - , Srifatunningsih; Harmin Sulistyaning Titah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Climate change is a phenomenon caused by human activities that increase greenhouse gas emissions, particularly carbon dioxide (CO₂), thereby accelerating global warming. In Surabaya City, the Surabaya River serves as a primary raw water source for the local water utility (PDAM). However, land-use changes in the riparian zone—from Green Open Spaces (RTH) to residential and industrial areas—have reduced environmental carrying and buffering capacities due to rising CO₂ emissions. This study aims to analyze the CO₂ absorption capacity of RTH in the riparian zone of the Surabaya River, specifically in the Sepanjang – Gunungsari segment. The methods used include literature review, collection of primary and secondary data, and analysis of RTH suitability based on applicable regulations. The calculation of CO₂ absorption capacity considered the area of existing RTH and the types of vegetation present. The results show that the existing RTH area is only 63,000 m², significantly below the ideal requirement of 124,857 m². With the current vegetation composition, the total CO₂ absorption capacity is estimated at 594,628.69 kg CO₂ per year. These findings highlight the importance of maintaining and expanding RTH in riparian areas to support climate change mitigation in urban environments.